The Effect of Job Satisfaction On Sustainable Orientation: A Systematic Literature Review - Siti Handayani Maulidina; Ari Saptono; Darma Rika Swaramarinda (IKRAITH-EKONOMIKA, 2026)
This study aims to systematically examine the relationship between job satisfaction and sustainable orientation in the context of modern organizations. This literature review uses a Systematic Literature Review (SLR) approach, referring to the PRISMA guidelines. A total of 41 scientific articles published between 2020 and 2025 were qualitatively analyzed. The results of the review indicate that job satisfaction plays a significant role in shaping individual and organizational sustainability behavior. Employees who are satisfied with their jobs tend to demonstrate a higher commitment to sustainable practices, both in environmental, social, and economic aspects. Job satisfaction strengthens sustainable orientation through the mediation of organizational commitment, green HRM, and ethical climate.